The Role of Information Professionals in Protecting National History and Sovereignty - Wahieda Azman, Farah; Farik Mat Ya, Saiful; Aliaa Amanina Mohd Aminuddin, Nur; Ahmad Dzarawi, Nurhidayah; Azwan Azman, Kamarul; Pati Khan, Mazlina (International Journal of Engineering and Technology, 2018)
Protecting for sovereignty can be an effective tool in order to cope with relations between states, drawing boundaries of acceptable behavior. Itâ€™s also a way of judging the actions taken from a state, whose owns ultimate power that always make the principle of sovereignty expendable. Information professional today play critical roles to ensure that state sovereignty would be strengthening and protecting them from external pressure. This paper highlights the need to pay more attention to the aspects of sovereignty that related with information professional roles and issues of Malaysianâ€™s neighboring country. Ignoring these aspects of sovereignty will lead to the issues that can threaten national sovereignty and peace.Â